Pole placement and LQR implementation on longitudinal altitute holding control of wing in surface effect vehicle - Muhammad Nanda Setiawan; Evan Rizky Suryana; Leo Parytta; William Andaro (Journal of Mechatronics, Electrical Power and Vehicular Technology, 2020)
The longitudinal altitude holding control system (LAHCS) of wing in surface effect (WiSE) vehicle has been developed using Simulink/Matlab. The LAHCS is designed to maintain the altitude of the vehicle stands at 1 m above the surface, with a maximum allowable deviation of 0.5 m. The purpose is to gain an additional lift generated by the surface effect to increase the aerodynamic performance. This control system is investigated using two approaches, i.e., the pole placement and the linear quadratic regulator (LQR) methods. Originally, the system shows an unstable response on the phugoid mode, indicated by the positive value of its Eigen. After the pole placement method is applied, the system is stable and capable of maintaining the reference command altitude. This method produces 0.27 of the maximum altitude deviation when the disturbance, represented by the doublet input elevator ±5° is applied. Moreover, the time needed for the system to reach the steady-state response of altitude is around 2.2 seconds. In comparison, the LQR method is also applied to the system with the same scenario. Although the settling time response is quite similar to the previous result, its maximum altitude deviation is significantly reduced by around 80 %. In conclusion, both of the methods used to design the LAHCS are capable of maintaining the altitude of the WiSE vehicle always below its maximum deviation tolerance.